Osobennosti metodiki uskorennogo obycheniya i sovershenstvovaniya tekhnicheskoi podgotovki bokserov v vyze - Strelnikov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
There was the task in front of the trainers of university's sports specializations to search the ways of successful training of the sportsmen. It is the constant stimulus of their active research activity in all of the specializations, and in boxing. The significant effect in comprehension, development and perfection of expedients is given by work of the boxer with the coach on palms. These impacts are put widely in a slowed-up way and halfpowered with correct execution of movements of hands and trunk. The regular employment on palms raises interest and promotes the fastest becoming of sports skills. These occupations in parallel solve also basic task of training process - organization of morning physical jerks of the boxer.